Moderating effect of Institutions on Financial Sector Development and Economic Growth Nexus in Nigeria. - Hamza Namadina; Lukman Lawali (Social Empowerment Journal, 2025)
This study examines the nexus between financial sector development and economic growth with institutions as a moderating variable. The study uses quarterly data from 2010q1 to 2022q4 to evaluate the long run relationship between the financial sector and economic growth using the methodology of autoregressive distributed lag models, the bounds test for cointegration with structural breaks. The study finds that institutions moderate the relationship between financial sector development and economic growth in Nigeria with the coefficients of institution having a statistically significant positive relationship with the economic growth. The study therefore finds that with good institutions such as good governance quality and control of corruptions the effect of financial sector development on economic growth could be felt on the economy. The study therefore recommends that the government should strengthen its institutions such as ensuring governance quality by making those in control of governance to be accountable and control corruption in the country by ensuring that all those found guilty of the offense are punished according to the laws of the land.